2018
DOI: 10.1016/j.jri.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with adverse pregnancy outcomes in women with systematic lupus erythematosus

Abstract: The aim of this prospective study was to determine clinical factors associated with adverse pregnancy outcomes in women with systematic lupus erythematosus (SLE). Fifty-six pregnancies from 46 women with SLE were enrolled. Risk factors for pregnancy loss, premature delivery, hypertensive disorders of pregnancy (HDP), and light-for-date neonate (LFD), were evaluated. Univariate and multivariate logistic regression analyses revealed a history of two or more pregnancy losses before 10 gestational weeks (GW) (OR 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
2
18
2
Order By: Relevance
“…In the present study, the following parameters were listed as candidate confounders based on previous reports: hypertension, aPL, SLEDAI, GC dose and concomitant immunosuppressant usage. [5][6][7][8][9][10][11]14,15 Final confounders for the conditional logistic regression analysis were selected based on the results of the univariate analysis. Missing data were not complemented in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the following parameters were listed as candidate confounders based on previous reports: hypertension, aPL, SLEDAI, GC dose and concomitant immunosuppressant usage. [5][6][7][8][9][10][11]14,15 Final confounders for the conditional logistic regression analysis were selected based on the results of the univariate analysis. Missing data were not complemented in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only half of the pregnancies after the diagnosis ended in live births, while previous reports have shown that 77-99% of the pregnancies after diagnosis ended in live births. 14,15,22,25 Some reports have shown disease activity, APS and GC usage as predictors for APOs. 14,15 In the present study, patients becoming pregnant after diagnosis showed a higher prevalence of aPL with higher GC dose and tended to have higher disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucocorticoids are associated with an increased risk of premature birth and some reports have suggested that this increased risk is independent of disease activity 10,82 . Some studies in SLE have detected an association between these drugs and premature rupture of the amniotic sac (known as rupture of membranes) surrounding the baby 83 , but other studies did not detect this association [84][85][86] . Fluorinated corticosteroids are not metabolised by the placenta and cross the placental barrier 87 , so these drugs should be used for fetal indications only.…”
Section: [H1] Medicationmentioning
confidence: 99%
“…A variety of factors may be related to fetal and maternal adverse outcomes, among which disease activity is the most concerned 5 . Lupus nephritis has been shown to increase the risk of hypertension disorders of pregnancy in SLE women 6 , and even those with previous renal flare were reported to have increased incidence of eclampsia 7 and FGR 8 . Consequently, SLE women is recommended to consider pregnancy during periods of inactive or stable disease 9 , because active disease has been displayed as an important predictor for poor pregnancy outcomes 10 , while a remission at least six months before conception could reduce the risk of unfavorable pregnancy outcomes 11 .…”
Section: Introductionmentioning
confidence: 99%